A Si/Ge nanocomposite prepared by a one-step solid-state metathesis reaction and its enhanced electrochemical performance1. Issue 21 (7th June 2015) - Lin, Ning; Wang, Liangbiao; Zhou, Jianbin; Zhou, Jie; Han, Ying; Zhu, Yongchun; Qian, Yitai; Cao, Changhe
<x xml:space="preserve">Abstract</x> High-performance Si/Ge anodes are prepared through a one-step solid-state metathesis reaction between Mg2Si and GeO2 for the first time.